Cationic antimicrobial peptide CC34 potential anticancer and apoptotic induction on cancer cells - Liqiang Dong; Yunhe Li; Yaguang Zhang; Shi Su (Amino Acids)
Abstract To evaluate the potential of antimicrobial peptide CC34 for use as therapeutic agents for gastric cancer SGC-7901 and hepatocellular carcinoma HepG-2. In this study, the antibacterial activity and antibacterial mechanism were tested by the minimum inhibitory concentration (MIC) analysis, minimal bactericidal concentration (MBC) analysis, bacterial biofilm and NaCl permeability assays. Then, we assessed the hemolytic activity and cytotoxicity of CC34 for red blood cells and cancer cells, respectively. Apoptosis assay, cell cycle analysis, determination of intracellular ROS, western blot analysis caspase activity assay and ATP assay were further performed to investigate the mechanism of CC34 affected cancer cells. The novel peptide could inhibit Gram-negative and Gram-positive bacteria, with low hemolytic activity against mouse and chicken erythrocytes. Moreover, CC34 exhibited higher inhibitory activity against biofilm formation. In addition, our data showed that CC34 significantly suppressed cell proliferation, in a dose dependent manner. CC34 induced apoptosis, induced reactive oxygen species (ROS) generation, inhibited B-cell lymphoma-2 (Bcl-2) expression, increase B-cell lymphoma protein 2 associated X protein (Bax) expression, release of cytochrome c (Cyt C), promoted caspase-3 and − 9 activities and reduced cellular ATP levels in cancer cells. Our results indicate that CC34 with antimicrobial activity have a highly potent ability to induced apoptosis via mitochondrial-mediated apoptotic pathway in cancer cells.